Piecza zastępcza jako element systemu pomocy rodzinie – na przykładzie gminy Poznań - Zaremba-Stanulewicz, Joanna (Studia Prawa Publicznego, 2025)
The text brings together the legal basis and assumptions of foster care. This is an institution regulated under Polish law by the Act of 9 June 2011 on Family Support and the Foster Care System (consolidated text Journal of Laws of 2025, item 49). Foster care is used to provide care for a child and carry out the educational process in conditions that are as favourable as possible for the minor, often in conditions quite similar to those of a properly functioning biological family. The purpose of custody is to protect the child’s interests and well-being when the biological parents are unable to provide appropriate conditions for his or her upbringing. This is a solution used when other available support measures have failed. As part of foster care, the child is temporarily placed with a foster family, who provide care until the parents can take over their educational responsibilities again. It should be noted that foster care differs from adoption – it is a temporary solution that assumes the child will return to the biological parents as soon as possible. The article also discusses the forms of foster care and its most important features and conditions. Particular attention is paid to how the foster care system functions in Poznań municipality and the problems associated with it, which in turn reflect the difficulties faced by foster families and foster care organizers nationwide.